Cellulose-based lithium battery diaphragm and preparation method thereof
By coating the slurry of porous alumina and nanocellulose on the lithium-ion battery separator, the problems of poor thermal stability and insufficient mechanical strength of traditional separators at high temperatures are solved, and higher cycle stability and charge and discharge efficiency are achieved.
Patent Information
- Application Number
- CN202510000021.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-01
- Publication Date
- 2025-04-04
AI Technical Summary
Traditional polyolefin lithium-ion battery separators have poor thermal stability at high temperatures, are prone to shrink or melt, and are limited wettability and mechanical strength, which easily breaks and increases the risk of short circuits inside the battery.
A cellulose-based lithium battery separator is used to form a coating by coating a slurry composed of porous alumina and nanocellulose on the base film to improve the ionic conductivity, thermal stability and mechanical strength of the separator.
It improves the cycle stability and charge and discharge efficiency of lithium batteries, enhances the thermal stability and mechanical strength of the diaphragm, and reduces the risk of short circuit inside the battery.
Smart Images

Figure CN119764742A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a cellulose-based lithium battery separator and a preparation method thereof. Background Art
[0002] In the context of the ever-increasing demand for energy today, lithium-ion batteries, as a key technology for modern energy storage, have been widely used in many fields. As one of the key components of batteries, the performance of lithium-ion battery separators plays a vital role in battery safety, cycle life and energy density. However, traditional polyolefin separators have obvious limitations. On the one hand, they have relatively poor thermal stability and are prone to shrinkage or even melting at high temperatures, resulting in contact between the positive and negative electrodes, short circuits, and safety accidents. On the other hand, due to poor wettability and limited mechanical strength, they are easily broken by external forces during battery assembly and use, increasing the risk of internal short circuits in the battery. Summary of the invention
[0003] In view of the deficiencies of the prior art, the object of the present invention is to provide a cellulose-based lithium battery separator.
[0004] Another object of the present invention is to provide a method for preparing the above-mentioned cellulose-based lithium battery separator.
[0005] Another object of the present invention is to provide a slurry.
[0006] The purpose of the present invention is achieved through the following technical solutions.
[0007] A cellulose-based lithium battery separator comprises: a base film and a coating on the base film, wherein the coating comprises: porous alumina and nanocellulose, wherein the ratio of the porous alumina to the nanocellulose is (10-25):(10-25) by mass, the particle size of the porous alumina is D50: 0.4-0.6 μm, and the nanocellulose is one of cellulose nanofibers (CNF) and cellulose nanocrystals (CNC).
[0008] In the above technical solution, the specific surface area of porous alumina is 20 to 30 m 2 / g, the pore diameter of the porous alumina is 5-15 nm, and the porosity of the porous alumina is 60-80%.
[0009] In the above technical solution, the particle size of nanocellulose is D50: 0.3-0.5 μm, and the specific surface area of nanocellulose is 40-60 m 2 / g, the pore size of nanocellulose is 20-40nm.
[0010] The preparation method of the cellulose-based lithium battery diaphragm comprises: coating the slurry on the base film, drying, obtaining a coating on the base film, and obtaining the cellulose-based lithium battery diaphragm, wherein the base film is a hydrophilic film.
[0011] In the above technical solution, the method for preparing the hydrophilic film includes: first soaking the PE film in acetone, then washing it with ethanol and water in sequence, drying it, and finally treating it with a plasma processor to remove surface organic matter and impurities to obtain a hydrophilic film with a negatively charged surface.
[0012] In the above technical solution, the coating speed is 20 to 60 m / min.
[0013] In the above technical solution, the thickness of the coating is 2 to 3 microns.
[0014] A slurry comprises: porous alumina, nanocellulose, water, a dispersant and a binder. The ratio of the porous alumina, nanocellulose, water, the dispersant and the binder is (10-25): (10-25): (50-70): (0.2-0.5): (5-10) by mass.
[0015] In the above technical solution, the particle size of the slurry is D50: 0.4-0.6 microns, D90: 0.8-1.2 microns.
[0016] In the above technical solution, the dispersant is ammonium polyacrylate.
[0017] In the above technical solution, the binder is an acrylate copolymer solution, and the content of the acrylate copolymer in the acrylate copolymer solution is 50 to 90 wt %.
[0018] In the above technical solution, the ratio of porous alumina, nanocellulose, water, dispersant and binder is preferably (10-14): (16-25): (50-70): (0.2-0.5): (5-10) by mass.
[0019] The method for preparing the slurry comprises: mixing porous alumina, nanocellulose, water, a dispersant and a binder until they are uniform to obtain the slurry.
[0020] The method for preparing the above slurry specifically comprises the following steps:
[0021] Step 1, mixing water, a dispersant, porous alumina and nanocellulose until uniform to obtain a first solution;
[0022] In step 1, water, a dispersant, porous alumina and nanocellulose are mixed, and stirred at a rotation speed of 1500 to 2500 r / min and a revolution speed of 40 to 60 r / min for 10 to 30 minutes until the mixture is uniform, thereby obtaining a first solution.
[0023] Step 2: Mix the first solution and the binder until they are uniform to obtain a slurry.
[0024] In step 2, the first solution and the binder are mixed, and stirred and ultrasonicated for 15 to 25 minutes in a vacuum environment until they are uniform to obtain a slurry, wherein the stirring rotation speed is 1200 to 4000 r / min, the revolution speed is 30 to 50 r / min, the ultrasonic frequency is 5 to 10 kHz, and the vacuum degree of the vacuum environment is 130 to 1300 Pa.
[0025] Application of porous alumina and nanocellulose to synergistically improve the ionic conductivity, needle puncture strength, liquid absorption rate and / or liquid retention rate of the separator.
[0026] Application of porous alumina and nanocellulose to synergistically improve the thermal stability of membranes.
[0027] Application of porous alumina and nanocellulose to synergistically improve the capacity retention rate of lithium-ion batteries.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention forms a cellulose-based lithium battery separator by coating a slurry containing nanocellulose and porous alumina on the surface of a base film. Nanocellulose and porous alumina have a porous structure and a uniform pore distribution, which can make the lithium ion fluid concentrate at a specific position on the electrode surface, which is conducive to the deposition of lithium ions. Nanocellulose has a widely distributed pore structure, which is easy to produce uniform lithium ions, thereby improving the ionic conductivity of the cellulose-based lithium battery separator, so that Li ions can be uniformly deposited and oxidized during battery cycling, thereby improving the cycle stability of the lithium battery. Porous alumina has a high melting point, thermal stability and mechanical strength, and can provide additional support and guarantee for the cellulose-based lithium battery separator, so that the cellulose-based lithium battery separator also has a high thermal stability and a low shrinkage rate at a high temperature of 150°C. At the same time, the porosity of porous alumina is high, which provides abundant channels for the transmission of lithium ions, shortens the transmission path of lithium ions, and allows lithium ions to pass through the separator quickly, thereby improving the charge and discharge efficiency of the battery.
[0030] 2. The nanoscale fiber structure of nanocellulose can make the electrolyte evenly distributed in the diaphragm, avoid the situation of uneven local electrolyte concentration, and ensure that the charging and discharging reactions of the lithium battery in different parts can be carried out evenly, further improving the performance stability of the battery. The surface of nanocellulose is rich in hydroxyl polar groups, which makes it have good hydrophilicity, can fully contact with the electrolyte and quickly absorb the electrolyte. This is conducive to reducing the transmission impedance of lithium ions in the diaphragm and improving the ionic conductivity. The diaphragm of the present invention maintains a spherical shape in the contact angle test and is easy to spread out, covers a large surface and is easily absorbed, and has good wettability. Good wettability ensures that the electrolyte is easily and quickly distributed to the pores of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of lithium ion deposition in Comparative Example 6 and Example 5, Figure 1 a is a schematic diagram of Li ion deposition in Comparative Example 6, Figure 1 b is a schematic diagram of Li ion deposition in Example 5;
[0032] Figure 2 The electron microscope image (15,000 times) of the diaphragm prepared from the slurry of Example 2 is shown. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0034] Nanocellulose (powder): Hubei Dali Chemical Co., Ltd.;
[0035] Porous alumina (powder): Suzhou Jinyi New Materials Technology Co., Ltd.;
[0036] Acrylate copolymer solution: Ningbo Xinfei Plastic Chemical Co., Ltd.;
[0037] Ammonium polyacrylate: Shanghai Sanrui Polymer Materials Technology Co., Ltd.
[0038] Nanocellulose is a new type of material, a nanoscale fibrous material extracted from natural cellulose. It has a unique structure, high specific surface area and thermal stability. Its nanoscale structure enables it to interact better with other materials at the microscopic level. At the same time, nanocellulose has excellent mechanical strength, which can enhance the puncture resistance and tensile properties of the separator.
[0039] The parameters of nanocellulose in the following examples and comparative examples are as follows:
[0040]
[0041] The parameters of the porous alumina in the following examples and comparative examples are as follows:
[0042]
[0043] Double planetary mixer: XFZH-30L.
[0044] In the following examples, water is pure water.
[0045] The thickness of the base film in the following embodiment is 9 μm. The method for preparing the base film (hydrophilic film) includes: soaking the PE film in acetone for 12 hours, washing it with ethanol and water in turn, drying it in a 40°C oven for 30 minutes, and finally treating it with a plasma processor for 60 seconds to remove surface organic matter and impurities to obtain a hydrophilic film with a negative charge on the surface (after the surface of the membrane is negatively charged, there is electrostatic repulsion between it and pollutants such as electrolytes with negatively charged functional groups, which can reduce the adsorption and deposition of organic matter on the surface of the membrane, thereby reducing the degree of membrane pollution. The greater the charge density on the surface of the membrane, the stronger the hydrophilicity of the membrane, thereby improving the affinity of the membrane for water). The power of the plasma processor is 50W, and the gas introduced into the plasma processor during operation is O 2 and N 2 Mixed gas, by volume, O 2 and N 2 The ratio is 1:1.
[0046] In the following embodiments, the electrolyte is a mixture of an electrolyte and a solvent, the electrolyte is lithium hexafluorophosphate (the concentration of the electrolyte in the electrolyte is 1 mol / L), and the solvent is a mixture of ethylene carbonate, propylene carbonate and dimethyl carbonate (volume ratio is 1:1:1).
[0047] Examples 1 to 3
[0048] A method for preparing a slurry comprises the following steps:
[0049] Step 1, mixing water, a dispersant, porous alumina and nanocellulose in a double planetary mixer, stirring at a rotation speed of 2500 r / min and a revolution speed of 40 r / min for 15 minutes until uniform, to obtain a first solution, wherein the dispersant is ammonium polyacrylate, and the nanocellulose is cellulose nanofiber (CNF);
[0050] Step 2, mixing the first solution and the binder, stirring and ultrasonicating them simultaneously in a double planetary mixer under a vacuum environment for 15 minutes until they are uniform (the stirring rotation speed is 1500r / min, the revolution speed is 40r / min, the ultrasonic frequency of the ultrasound is 5kHz, and the vacuum degree of the vacuum environment is 1000pa) to obtain a slurry, wherein the binder is an acrylate copolymer solution, the content of the acrylate copolymer in the acrylate copolymer solution is 70wt%, and the acrylate copolymer is polymerized by acrylate and vinylidene fluoride (the degree of polymerization is 5000), and the ratio of porous alumina, nanocellulose, water, dispersant and binder is X in parts by mass.
[0051] The X values are shown in Table 1.
[0052] Table 1
[0053] Slurry X Example 1 15:15:60:0.5:9.5 Example 2 10:20:60:0.5:9.5 Example 3 20:10:60:0.5:9.5
[0054] The particle size of the slurry prepared in Example 1 is D50: 0.477 microns, D90: 1.032 microns; the particle size of the slurry prepared in Example 2 is D50: 0.443 microns, D90: 1.125 microns; the particle size of the slurry prepared in Example 3 is D50: 0.421 microns, D90: 1.123 microns.
[0055] Comparative Example 1
[0056] A method for preparing slurry, comprising: mixing porous alumina, water and a dispersant in a double planetary mixer, stirring for 15 minutes at a rotation speed of 2500 r / min and a revolution speed of 40 r / min, adding a binder, stirring and ultrasonicating in a double planetary mixer for 15 minutes in a vacuum environment until uniform (the rotation speed of stirring is 1500 r / min, the revolution speed is 40 r / min, the ultrasonic frequency of the ultrasonication is 5 kHz, and the vacuum degree of the vacuum environment is 1000 Pa), to obtain a slurry. In terms of mass fractions, the ratio of porous alumina, water, dispersant and binder is 30:60:0.5:9.5. The dispersant and binder are the same as those in Example 1.
[0057] The particle sizes of the slurry prepared in Comparative Example 1 are D50: 0.479 microns and D90: 1.124 microns.
[0058] Comparative Example 2
[0059] A method for preparing a slurry is substantially the same as that of Comparative Example 1, except that "porous alumina" is replaced by "conventional alumina (non-porous alumina)". The particle size of conventional alumina (powder) is D50: 0.489 microns, and the specific surface area is 34 m 2 / g, pore size is 5.45nm.
[0060] The particle sizes of the slurry prepared in Comparative Example 2 are D50: 0.487 microns and D90: 1.257 microns.
[0061] Comparative Example 3
[0062] A method for preparing a slurry, comprising: mixing conventional alumina (the same as the conventional alumina of Comparative Example 2), nanocellulose, water and a dispersant in a double planetary mixer, stirring for 15 minutes at a rotation speed of 2500 r / min and a revolution speed of 40 r / min, adding a binder, stirring and ultrasonicating in a double planetary mixer in a vacuum environment for 15 minutes until uniform (the stirring rotation speed is 1500 r / min, the revolution speed is 40 r / min, the ultrasonic frequency of the ultrasonication is 5 kHz, and the vacuum degree of the vacuum environment is 1000 Pa), to obtain a slurry. In terms of mass fractions, the ratio of conventional alumina, nanocellulose, water, dispersant and binder is 20:10:60:0.5:9.5. Nanocellulose, dispersant and binder are the same as those in Example 1.
[0063] The particle sizes of the slurry prepared in Comparative Example 3 are D50: 0.456 μm, D90: 1.145 μm.
[0064] Comparative Example 4
[0065] A method for preparing slurry is basically the same as Example 1, except that "porous alumina" is replaced by "nano alumina". The particle size of nano alumina is D50: 52nm, and the specific surface area is 22.4m 2 / g, pore diameter is 11.5nm, and porosity is 67%.
[0066] The particle sizes of the slurry prepared in Comparative Example 4 are D50: 0.427 microns, D90: 0.978 microns.
[0067] Examples 4 to 6 and Comparative Examples 5 to 8
[0068] A lithium battery (a soft-pack battery with an area of 10 cm×10 cm and a thickness of 3 mm), comprising: a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises: a positive electrode collector (nickel foam) and a positive electrode coating loaded on the positive electrode collector (the positive electrode material in the positive electrode coating is lithium iron phosphate), and the negative electrode comprises: a negative electrode collector (copper foil) and a negative electrode coating loaded on the negative electrode collector (the negative electrode material in the negative electrode coating is graphite), and a method for preparing the separator comprises: placing a base film (hydrophilic film) on a coating machine for coating slurry, coating the slurry on one side of the base film (hydrophilic film) at a coating speed of 30 m / min, entering a drying device under the traction of a traction roller and drying at 60° C. for 3 minutes, obtaining a coating on the base film, and obtaining a separator, and the slurry is one of Examples 1 to 3 and Comparative Examples 1 to 4.
[0069] Table 2
[0070] Battery / Separator Slurry for preparing diaphragm Example 4 Example 1 Example 5 Example 2 Example 6 Example 3 Comparative Example 5 Comparative Example 1 Comparative Example 6 Comparative Example 2 Comparative Example 7 Comparative Example 3 Comparative Example 8 Comparative Example 4
[0071] The parameters of the diaphragm prepared from the slurry of Example 1 are as follows:
[0072]
[0073] The parameters of the diaphragm prepared from the slurry of Example 2 are as follows:
[0074]
[0075] The parameters of the diaphragm prepared from the slurry of Example 3 are as follows:
[0076]
[0077] The parameters of the diaphragm prepared from the slurry of Comparative Example 1 are as follows:
[0078]
[0079]
[0080] The parameters of the diaphragm prepared from the slurry of Comparative Example 2 are as follows:
[0081]
[0082] The parameters of the diaphragm prepared from the slurry of Comparative Example 3 are as follows:
[0083]
[0084]
[0085] The parameters of the diaphragm prepared from the slurry of Comparative Example 4 are as follows:
[0086]
[0087] At a current density of 0.3C, the capacity retention rate of the lithium battery in Example 4 after 500 cycles is 91.3%, and the capacity retention rate after 200 cycles is 93.1%; the capacity retention rate of the lithium battery in Example 5 after 500 cycles is 92%, and the capacity retention rate after 200 cycles is 95.3%; the capacity retention rate of the lithium battery in Example 6 after 500 cycles is 87.3%, and the capacity retention rate after 200 cycles is 89.4%; the capacity retention rate of the lithium battery in Comparative Example 5 after 500 cycles is 92%, and the capacity retention rate after 200 cycles is 95.3%. The capacity retention rate of the lithium battery in Comparative Example 6 is 80.1% after 500 cycles, and 82.5% after 200 cycles; the capacity retention rate of the lithium battery in Comparative Example 7 is 85.4% after 500 cycles, and 88.3% after 200 cycles; the capacity retention rate of the lithium battery in Comparative Example 8 is 83.5% after 500 cycles, and 85.6% after 200 cycles.
[0088] Figure 1 Schematic diagram of lithium ion deposition in Comparative Example 6 and Example 5, Figure 1 a is a schematic diagram of Li ion deposition in Comparative Example 6, Figure 1 The coating of the separator in a has a non-uniform pore distribution, and the Li ions are concentrated at specific locations on the electrode surface, resulting in local Li nucleation ( Figure 1 The "atomic nucleus" in a), the crystal growth forms a local lithium dendrite structure, which is not conducive to Li ion deposition. Figure 1 b is a schematic diagram of Li ion deposition in Example 5, Figure 1 The coating of the separator in b has a uniform pore distribution, lithium ions flow to the electrode surface more evenly, the Li nucleation process is more uniform, and no lithium dendrites are formed.
[0089] Figure 2 The electron microscope image (15,000 times) of the diaphragm prepared from the slurry of Example 2 is shown in FIG. Figure 2 It can be seen that the nanocellulose in the coating has a widely distributed pore structure.
[0090] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A cellulose-based lithium battery separator, characterized in that: include: The base film and the coating on the base film, the coating includes: porous alumina and nanocellulose, the ratio of porous alumina to nanocellulose is (10-25): (10-25) by mass, the particle size of the porous alumina is D50: 0.4-0.6 μm, and the nanocellulose is one of cellulose nanofibers and cellulose nanocrystals.
2. The cellulose-based lithium battery separator according to claim 1, characterized in that: The specific surface area of porous alumina is 20 to 30 m 2 / g, the pore diameter of the porous alumina is 5-15 nm, and the porosity of the porous alumina is 60-80%.
3. The particle size of nanocellulose is D50: 0.3-0.5 μm, and the specific surface area of nanocellulose is 40-60 m 2 / g, the pore size of nanocellulose is 20-40nm.
4. The method for preparing a cellulose-based lithium battery separator according to any one of claims 1 to 3, characterized in that: include: The slurry is coated on a base film and dried to obtain a coating on the base film to obtain a cellulose-based lithium battery separator, wherein the base film is a hydrophilic film.
5. The preparation method according to claim 4, characterized in that: The method for preparing a hydrophilic film includes: firstly soaking the PE film in acetone, then washing it with ethanol and water in sequence, drying it, and finally treating it with a plasma processor to remove surface organic matter and impurities to obtain a hydrophilic film with a negatively charged surface.
6. A slurry, characterized in that: include: The porous alumina, nanocellulose, water, dispersant and binder are present in a ratio of (10-25): (10-25): (50-70): (0.2-0.5): (5-10) by mass.
7. The method for preparing the slurry according to claim 6, characterized in that: include: The porous alumina, nanocellulose, water, a dispersant and a binder are mixed until uniform to obtain a slurry.
8. Application of porous alumina and nanocellulose to synergistically improve the ionic conductivity, needle puncture strength, liquid absorption rate and / or liquid retention rate of the membrane.
9. The application of porous alumina and nanocellulose to synergistically improve the thermal stability of the membrane.
10. The application of porous alumina and nanocellulose to synergistically improve the capacity retention rate of lithium-ion batteries.
Citation Information
Patent Citations
Ultra-light ceramic mixed coating diaphragm slurry and preparation method thereof
CN111525077A
Modified ceramic diaphragm as well as preparation method and application thereof
CN116435710A
Lithium battery diaphragm as well as preparation method and application thereof
CN116565456A
Porous alumina powder for lithium ion battery, battery diaphragm, battery and electric equipment
CN119038966A